A Study of Cd SnO Thin Film Deposited at Low Temperature using Reactive Magnetron Sputtering - Dudonis, J.; Jotautis, A.; Naujokaitis, R. (Elektronika ir Elektrotechnika, 2003)
Transparent conductive oxide coatings will underpin the development of the next generation of photovoltaic solar cells, flat panel displays, and optoelectronic components. As alternative, the cheaper coating material Cd SnO (TCO) can be used instead of indium tin oxide. The optical and electrical properties of CTO coatings are, though, notoriously sensitive to process parameters and depend on control of film composition, structure, crystallinity, defect density, surface roughness, and dopant concentration. The paper presents results of experimental study of magnetron deposition process. Transparency and electrical conductivity of deposited films most depends on magnetron discharge voltage, work gas O2 + Ar composition and substrate potential (bias). The minimum of sheet resistance was obtained at particular voltage, and this voltage depends on work gas composition. Transparency depends on discharge voltage to a lesser degree and drops only in short wave edge at larger discharge voltage. The area of optimal technological parameters where quality layers with proper characteristics for conductive electrodes can be formed was determined by analysis of experimental results. Ill. 7, bibl. 5 (in English; summaries in Lithuanian, English and Russian).